Persepsi Wisatawan Domestik dan Mancanegara terhadap Pengelolaan Daya Tarik Wisata Jatiluwih, Kabupaten Tabanan, Provinsi Bali - Dewa Ayu Diyah Sri Widari (Sekolah Vokasi, Universitas Gadjah Mada, 2021)
Jatiluwih Tourism Attraction as part of the World Cultural Heritage is a tourist product consumed by tourists. Perception of tourists is important to be studied as a reference in the management of tourist attractions. Data collection techniques using survey methods are used to determine tourists' perception of Jatiluwih Tourism Attraction as part of the World Cultural Heritage. Questionnaires are used as research instruments to obtain information from tourists. After the data is collected, then the measurement is done using the Likert Scale. In determining the number of tourist samples used Slovin formula. Based on Slovin formula with a tolerance limit of 5%, the number of samples for foreign tourists as many as 204 people, and the number of samples for domestic tourists as many as 52 people. The total sample count was 256 people. Domestic and foreign tourists give the highest perception of employment opportunities for the community from the management of tourist attractions. Good perception of tourists is also given to the friendliness of the staff in providing service, naturalness and beauty of the scenery around the tourist attraction. The perception of tourists is not good given to the price of souvenirs, ease of access to the internet, availability of souvenirs with local characteristics, and smooth traffic around tourist attractions.